Direct measurement of cardiac stiffness using echocardiographic shearwave imaging during open‐chest surgery: A pilot study in human. Issue 5 (10th May 2020) - Saloux, Eric; Gauthier, Michael; Buklas, Dimitrios; Saplacan, Vladimir; Denoyer, Antoine; Labombarda, Fabien; Raitiere, Olivier; Criton, Aline; Milliez, Paul; Bauer, Fabrice
Abstract: Purpose: Cardiac stiffness is a marker of diastolic function with a strong prognostic significance in many heart diseases that is not measurable in clinical practice. This study investigates whether elastometry, a surrogate for organ stiffness, is measurable in the heart using ShearWave Imaging. Methods: In 33 anesthetized patients scheduled for cardiac surgery, ShearWave imaging was acquired epicardially using a dedicated ultrasound machine on the left ventricle parallel to the left anterior descending coronary artery in a loaded heart following the last cardiac beat. Cardiac elastometry was measured offline using the Young modulus with customized software. Results: Overall, the ejection fraction was 61 ± 10%. E / A and E / e ′ ratios were 1.0 ± 0.5 and 10.5 ± 4.1, respectively. Cardiac elastometry averaged 15.3 ± 5.3 kPa with a median of 18 kPa. Patients with high elastometry >18 kPa were older ( P  = .04), had thicker ( P  = .02) but smaller LV ( P  = .004), had larger left atria ( P  = .05) and a higher BNP level ( P  = .04). We distinguished three different transmural elastometry patterns: higher epicardial, higher endocardial, or uniformly distributed elastometry. Conclusion: Elastometry measurement was feasible for the human heart. This surrogate for cardiac stiffness dichotomized patients with low and high elastometry, and provided three different phenotypes of transmural elastometry with link to diastolic function.